Pengaruh Kompetensi Mengajar Guru dan Fasilitas Belajar di Rumah pada Masa Pandemi Covid-19 terhadap Motivasi Belajar Siswa di SMAS Bina Siswa Kabupaten Rokan Hilir - Nurmala Syafitri; R.M Riadi; Hendripides Hendripides (Journal on Education, 2023)
This study aims to determine the Effect of Teacher Teaching Competence and Learning Facilities at Home on Student Learning Motivation at SMA Bina Siswa. The method used in this research is descriptive quantitative method with a population of 60 students and taking the entire population. The data collection instrument used in this study was a questionnaire in the form of a Google form that used a Likert scale for the independent variables, namely teacher teaching competence (X1) and home study facilities (X2). The analysis technique used is multiple linear regression. The research results obtained show that the teaching competence of teachers and learning facilities at home simultaneously affect student learning motivation. Based on the results of the analysis, the calculation shows the value of Fcount > Ftable (25.144> 3.16). Meanwhile, partially the teaching competence of teachers and learning facilities in the house has an effect on student learning motivation in student development high school in Rokan Hilir district. This is based on the results of the t test, the teacher teaching competence variable obtained a tcount of 6.690 with a ttable value of 2.001 and home learning facilities obtained a tcount of 6.541 with a ttable value of 2.001. So it can be concluded that the teacher's teaching competence and learning facilities at home have an effect on student learning motivation with a contribution of 60.8% and the remaining 38.2% is influenced by variables not examined.